An Enhanced Nickel Recovery from Mixed Hydroxide Precipitate Through Selective Leaching with KMnO4 Oxidant - Gumelar, Muhammad Dikdik; Rahayu; Saputra; Agustanhakri; Husin; Andrameda; Taqwatomo; Putra; Indrijarso; Saudi; Indriasari; Arfiana; Yuliani; Mumtaz; Mirahati (Jurnal Sains Materi Indonesia, 2024)
Mixed Hydroxide Precipitate (MHP), a metal precipitate with the dominant nickel and cobalt content in hydroxide compounds, can be leached as a lithium battery precursor. In this study, KMnO4 was used as an oxidant agent to increase the solubility of Ni and Co. The variation of the sulfuric acid concentration (0.5 - 1.5 M) as a leachate reagent, the concentration of KMnO4 (2.5 - 7.5 g/L), and the selective leaching temperature (60 - 80°C) were investigated. Solvent extraction using CYANEX 272 and D2EHPA was performed to separate the Ni, Co, and Mn. Atomic Absorption Spectrometry (AAS), Inductively coupled plasma mass (ICP-OES), and X-ray Fluorescence (XRF) were used to analyze the chemical compositions. At the same time, crystallographic analysis was observed with X-Ray Diffraction. It was observed that potassium permanganate increased the dissolution of Ni and Co to 91.3% and 85.4% but decreased the dissolution of Mn (37.53%) under the following conditions: 1.75 M sulfuric acid, 7.5 g/L potassium permanganate, and 60°C temperature. High purity of nickel crystal (99.64%) was observed with spontaneous nucleation due to the supersaturated nickel solution after solvent extraction with CYANEX 272. Thus, using permanganate ion as selective leaching of Ni and Co from Mn is promising.